Tensile strength of a novel superficial suture pattern compared to traditional suture patterns in a cadaveric human skin model. Issue 11 (November 2022) - Look, Nicole; Rodriguez Fontan, Francisco; Baldini, Todd H.; Lindeque, Bennie
Highlights: This is a cadaveric study testing the suture strength of commonly used skin closure patterns and a novel pattern. The horizontal-mattress pattern showed significantly less strength as compared to other suture patterns. The novel pattern demonstrated the greatest dehiscence force and tensile strength. Abstract: Background: The suture material and pattern utilized to maintain the skin edges in proximity allows for successful primary wound healing. No prior studies have evaluated the tensile strength of different suture patterns on human cadaveric skin. This study evaluates the tensile strength of four single suture patterns: simple (S), horizontal-mattress (HM), vertical-mattress (VM), and a novel stich termed Lindeque locking (LL). Methods: Four skin closure patterns were tested on human cadaveric skin using 3–0 nylon – S, HM, VM, LL – totaling four groups with twelve samples each. A tensioning device applied 1 N of force/second in a linear fashion. The primary outcome measures were: (i) wound dehiscence force, and (ii) ultimate load to failure. Statistics included one-way ANOVA with post-hoc Tukey tests. Results: The LL stitch had the greatest dehiscence force (198.60 N) and ultimate load to failure force (211.13 N) but was only significantly greater on both outcomes versus HM (104.81 N; 95% confidence interval [CI], 65.7 to 121.9; p < 0.001) and (120.79 N; 95% CI, 63.5 to 117.2; p  < 0.001), respectively. There was no significant difference between LL and S for dehiscence, nor for the ultimate load to failure (186.90 N and 195.08 N, respectively). The LL pattern was significantly greater for an ultimate load to failure, but not for dehiscence when compared to VM (173.9 N and 171.1 N, respectively). Of all patterns, HM had significantly less withstanding force. Conclusions: The Lindeque Locking stitch demonstrated the greatest dehiscence force and tensile strength. It may decrease the risk of wound dehiscence for high tension wounds.